Next welfare state? : UK welfare after Covid-19 - Pierson Christopher (Policy Press, 2021)
In this book, Chris Pierson argues that we will need to think quite differently about the British welfare state after COVID-19. He looks back to the welfare state's origins and development as well as forwards, unearthing some surprising solutions in unexpected places.